The Economic-Soteriological Dimension of the Doctrine of the Trinity in Pentecostal-Charismatic Perspective: A Biblical-Theological Inquiry - Petrus Ng; Nicodemus Welhelem Manuhutu; Gunawan (DIEGESIS: Jurnal Teologi Kharismatika, 2026)
This article examines the economic-soteriological dimension of the doctrine of the Trinity from a biblical-theological and Pentecostal-Charismatic perspective. It does not reject the classical ontological formulation of the Trinity, but clarifies how Scripture witnesses to the saving work of the Father, the Son, and the Holy Spirit in the economy of salvation. Using a qualitative biblical-theological method, the study analyzes Genesis 1:1-3, John 1:1-14, and 1 Corinthians 8:4-6 in dialogue with contemporary discussions on the relation between the immanent and economic Trinity. The study shows that Genesis 1:1-3 cautiously opens a theological horizon for the creative work of God’s Spirit without overreading the Old Testament as an explicit Nicene formula. John 1:1-14 presents high Logos Christology oriented toward incarnation and salvation, while 1 Corinthians 8:4-6 frames the Father and Jesus Christ within Christian monotheistic confession, worship, and life. From a Pentecostal-Charismatic perspective, Spirit baptism, testimony, and altar-centered soteriology are understood as lived participation in the triune economy of salvation. The article contributes a moderated synthesis that connects biblical theology, Trinitarian restraint, and Pentecostal spirituality. Abstrak Artikel ini mengkaji dimensi ekonomi-soteriologis doktrin Tritunggal dalam perspektif biblika-teologis dan Pentakostal-Karismatik. Kajian ini tidak menolak formulasi ontologis klasik tentang Tritunggal, tetapi memperjelas bagaimana Kitab Suci menyaksikan karya keselamatan Bapa, Anak, dan Roh Kudus dalam ekonomi keselamatan. Dengan metode kualitatif biblika-teologis, artikel ini menganalisis Kejadian 1:1-3, Yohanes 1:1-14, dan 1 Korintus 8:4-6 dalam dialog dengan diskusi kontemporer tentang hubungan Tritunggal imanen dan Tritunggal ekonomi. Hasil kajian menunjukkan bahwa Kejadian 1:1-3 membuka cakrawala teologis tentang karya kreatif Roh Allah tanpa membaca Perjanjian Lama secara berlebihan sebagai formula Nicea eksplisit. Yohanes 1:1-14 menampilkan Kristologi Logos yang tinggi dan berorientasi pada inkarnasi serta keselamatan, sedangkan 1 Korintus 8:4-6 menempatkan Bapa dan Yesus Kristus dalam pengakuan monoteistik, ibadah, dan kehidupan Kristen. Dalam perspektif Pentakostal-Karismatik, baptisan Roh, kesaksian, dan soteriologi altar dipahami sebagai partisipasi hidup dalam ekonomi keselamatan Allah Tritunggal. Artikel ini berkontribusi melalui sintesis moderat antara teologi biblika, kehati-hatian Trinitarian, dan spiritualitas Pentakostal.